ANALISIS MODEL PERENCANAAN DAN PENGENDALIAN PERSEDIAAN BABY PRODUCT STUDI KASUS DI PT. MULTI INDOCITRA, Tbk. - Rizal Ferdiansyah (Universitas Mercu Buana, 2018)
Company typically purchase products to meet annual needs with little regard for actual demand conditions, resulting in considerable overstock and high inventory costs. This research aims to control PT. Multi Indocitra, Tbk’s inventory by ABC analysis, demand forecasting method, and (y, R) EOQ. A total of 60 products of the company are 6 products with A classification, namely Breast Pump Electric Pro, Multi Function Sterilizer, Portable Breast Pump, Breast Pump Manual, Silicone Nipple Eco 48 + 6 Pcs Mix, and Home Baby Food Maker. Performed calculations with 4 methods of forecasting, namely single exponential smoothing, double exponential smoothing, trend analysis, and ARIMA. Based on the smallest MAD, MSE, and MAPE values, we obtain s-curve trend model for Breast Pump Electric Pro, Breast Pump Manual, Silicone Nipple Eco 48 + 6 Pcs Mix, and Home Baby Food Maker and quadratic trend model for Multi Function Sterilizer and Breast Pump Portable. The total inventory cost becomes more efficient than the actual condition.The results of product forecasting indicate a trend that increases linearly in the next period. (y, R) EOQ can assist company in lowering inventory levels. The calculation results and graphs of (y, R) EOQ indicate a stable trend and company inventory can be more controlled, so as to minimize overstock and stockout because ROP value already take into account of safety stock value.